السهو و الخطأ في التقارير المحاسبية و أثره على تحليل الأعمال التجارية - مصطفى, الحبيب (My University, 2020)
This study aims to clarify the meaning of accounting errors and so the commercial business and also show methods of how to reduce this accounting errors and chances of making mistakes and fraud to put controls and procedures to prevent. The problem of the study is the impact of accounting errors on the commercial business, besides ignorance of assumptions and accounting principles. And usage of accounting that can help a lot in the elimination and reduction of accounting errors, considering the accounting as an effective method to discover accounting errors. This study is one of the very few researches in auditing and accounting field. So we hope that this study will give an idea of the accounting errors and their impact on commercial business.
Keywords: الأخطاء المحاسبية،تأثير الأخطاء المحاسبية على الأعمال التجارية،كيفية تصحيح الأخطاء المحاسبية